(untitled) (Global Journal of Medical Research, 2015)
The world population is noting an increasing trend towards development of particular diseases like Obesity, hypertension, diabetes mellitus. Some of them are turning into modern epidemics. These diseases can occur in isolation. Recent trends suggest the interlink age of the disease patterns leading to development of syndromes. One such syndrome is the Metabolic Syndrome. The Metabo1ic Syndrome is one of the major public health issues of this century. It is constellation of physical conditions and metabolic abnormalities commonly found in association with increased risk for development of Type 2 diabetes mellitus , Cardiovascular disease and other medical conditions. The article Deals with the Medical and Biochemical events occurring as a result of this developing medical Illness.